Isolation and Identification Of Glycoside Compounds from n-Butanol Fraction of Red Pakoba (Syzygium sp.) - Gabriel Reinhard Kahiking; Rymond Rumampuk; Emma Pongoh (Jurnal Kimia Fullerene, 2020)
The red pakoba (Syzygium sp.) is a plant originating from north sulawesi that is often used by local people as a basic ingridient of medicine. This research was conducted to isolate and identify glycoside compounds contained in the n-butanol fraction of red pakoba fruits (Syzygium sp.). The isolation process was carried out using the maceration method, for the separation and purification of compounds using Thin Layer Chromatography (TLC) and Gravity Column Chromatography and obtained F2.4 sub-fraction isolates with a sample weight of 4.5 mg. Identification of compound using Proton Nuclear Magnetic Resonance (NMR-1H) and Carbon Nuclear Magnetic Resonance (NMR-13C) tecniques. The result of identification of isolate F2.4 sub-fraction as flavonoid glycoside compounds with the proposed name 3-O-methyl-butyrate-6,7,3',4' tetrahydroxy-5-methoxy-8-methyl flavan with molecular formula (C22H25O8)